Mood, sleepiness, and weight gain after three years on CPAP therapy for sleep apnoea. Issue 1 (1st January 2021) - Aro, Miia M.; Anttalainen, Ulla; Polo, Olli; Saaresranta, Tarja
ABSTRACT: Background: The prevalence of obstructive sleep apnoea syndrome (OSAS) keeps on rising. Daytime sleepiness resulting from fragmented sleep is the prime symptom, and obesity the major risk factor for OSAS. Quality of life with OSAS is often affected by depressive symptoms and anxiety. Nasal continuous positive airway pressure (CPAP) therapy reduces daytime sleepiness, but the results on the effect on mood, physical activity, and weight are controversial especially on long-term therapy. Purpose of this study was to evaluate these factors and predictors of weight gain during long-term CPAP therapy. Methods: Consecutive patients (n = 223), referred to sleep study with suspected OSAS, were enrolled. Patients underwent a cardiorespiratory polygraphy at baseline and a battery of questionnaires was completed, both at baseline, and after three years of follow-up. Total of 149 (67%; M 65, F 84) patients completed the follow-up. Of the 149 patients, 76 (51.0%; M 32, F 44) used CPAP. Results: In this study, depressive symptoms, anxiety, and sleepiness were alleviated during CPAP therapy. However, therapy did not have an influence on cravings of different food categories, or exercise habits and exercise duration. From the various factors studied, solely higher adherence to CPAP therapy was associated with weight gain. Conclusions: This research provides further evidence that long-term CPAP therapy in patients with OSAS not only decreases sleepiness and improves sleep quality but could also alleviate depressive symptoms and anxiety. In addition, our study reinforces that CPAP therapy alone is not sufficient for weight management in patients with OSAS. Regardless of comprehensive battery of questionnaires, we were unable to establish markers predicting weight gain during therapy. We advise on life-style counselling and weight management program to all patients with obesity on CPAP therapy.